A low-constraint, high-pressure air feed system for wind tunnel balances - Alexander, A. J. (College of Aeronautics, 1963)
A high-pressure air feed system, suitable for use with blowing models mounted on a six-component virtual-centre balance, is described. Air is supplied to the balance by a flexible ring main feed so that no air is lost as with an air-bearing system. Constraints on the balance are very low; at an internal pressure of 30 p.s.i. gauge with a mass flow of 0.5 lbs/sec. all force corrections were less than 1 lb., and the pitching moment correction less than 0.5 lb.ft. Rolling and yawing moment corrections were 2.0 lb.ft. and 2.7 lb.ft. respectively. The constraints were measured using a calibrator Which enabled the desired mass flow to be passed through the system without additional constraints.